The potential offered by smart cities to promote smart tourist destinations - Nezai, Azzeddine; Abdellah, Noureddine; Yazid, Kada (Technium Social Sciences Journal, 2021)
Abstract. The digital revolution has radically changed the world, as new digital technologies have introduced important innovations in factories, hospitals and schools, especially cities, improving the efficiency of city operations and life quality of its citizens and visitors. This study is a demonstration of the capabilities provided by smart cities to promote smart tourism through global experiences, where the study concluded that the inclusion of smart city determinants will make it a smart tourism destination and thus realize the concept of smart tourism as part of smart city, and improve the Provided tourism services quality and tourism experiences, since the innovation and sustainability are the only way to improve life quality and social value of both local residents and tourists.